Acceptance of medical drone technology and its determinant factors among public and healthcare personnel in a Malaysian urban environment: knowledge, attitude, and perception - Za’im Sahul Hameed, Muhammad; Nordin, Rosdiadee; Ismail, Aniza; Zulkifley, Muhammad Aidiel; Sham, Aina Suraya Helmy; Sabudin, Raja Zahratul Azma Raja; Zailani, Mohamed Afiq Hidayat; Saiboon, Ismail Mohd; Mahdy, Zaleha Abdullah (Frontiers in Public Health, 2023)
Unmanned Aerial Vehicles (UAV) are used for commercial, medical, public safety and scientific research purposes in various countries. This study aimed to explore the acceptance of medical delivery drones among medical practitioners as well as the public community in Malaysia using a Knowledge, Attitude and Perception (KAP) model and using statistical analysis to decrease uncertainty. Bivariate and multivariate analysis of the results was done in SPSS. A total of 639 respondents took part in the survey, out of which 557 complete responses were finally analyzed. The results showed that the overall acceptance rate for medical delivery drones was positive. The acceptance rate was significantly correlated with knowledge, attitude, and perception scores, but not with sociodemographic factors. Raising awareness and educating the medical as well as public communities regarding the potential role and benefits of the drone are therefore important in garnering support for drone usage for medical purposes.